1996
DOI: 10.1016/1044-0305(96)85610-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the electron affinities of C60, corannulene, and coronene by using the kinetic method

Abstract: Novel anions that contain one molecule each of C 60 and the polycyclic aromatic hydrocarbon coronene are generated in the gas phase by electron attachment desorption chemical ionization. Collision-induced dissociation reveals that these cluster ions are loosely bonded. Fragmentation of the mass-selected cluster anion yields, as the only products, the intact radical anions of the constituent molecules, namely, the C 60 radical anion and the coronene radical anion, in almost identical relative abundances. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 83 publications
7
35
0
1
Order By: Relevance
“…21 but in negative-ion LT-FAB-MS no useful molecular ion peak can be observed with that matrix. In accordance with the high electron affinity of C 60 (2.66 eV 25 ) and with observations made by others, 26 fullerene anions are in general more easily formed than their positive counterparts. This tendency becomes more pronounced for the dimers and, therefore, the FAB matrix should act as solvent and efficient electron donor.…”
Section: Methodssupporting
confidence: 89%
“…21 but in negative-ion LT-FAB-MS no useful molecular ion peak can be observed with that matrix. In accordance with the high electron affinity of C 60 (2.66 eV 25 ) and with observations made by others, 26 fullerene anions are in general more easily formed than their positive counterparts. This tendency becomes more pronounced for the dimers and, therefore, the FAB matrix should act as solvent and efficient electron donor.…”
Section: Methodssupporting
confidence: 89%
“…are well-known to be generally higher than the EAs for the more compact PAHs (Modelli et al 2006), as are the EAs for PAHs comprising one or more five-membered rings (Todorov et al 2008) and fullerenes. The EA for the compact and highly symmetric coronene molecule (C 24 H 12 ) has been established at about 0.5 eV (Betowski et al 2006;Carelli & Gianturco 2012;Chen et al 1996;Denifl et al 2005;Duncan et al 1999;Malloci et al 2005). Although various experimental studies on radical anion PAHs have been reported (Denifl et al 2005;Duncan et al 1999), it is anticipated that these species will be unstable under the conditions of our ESI source and Penning trap due to their low EA.…”
Section: Electron Affinity: Stability Of [Pah -H]mentioning
confidence: 99%
“…1 kann nicht intakt desorbiert werden, sondern zersetzt sich oberhalb 500 K zu Wasserstoff und Kohlenstoff. Im Einklang mit der geringen Elektronenaffinität von 1 (0.5 eV) [22] [24] -Austauschkorrelationsfunktion der KohnSham-Gleichungen verwendet. Die Wellenfunktionen wurden im Gauß-Basissatz TZVP mit dem Turbomole-Code erweitert.…”
unclassified